TINJAUAN YURIDIS UU NO.16 TAHUN 2019 MENURUT ASAS MONOGAMI DAN HUBUNGAN HUKUM DALAM PERKAWINAN - Mieke Angraeni Dewi (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
Marriage is a bond that gives birth to the family as one of the elements in social and state life, which is governed by the rule of law in written law (state law) and unwritten law (customary law). According to Law No. 16 of 2019 marriage and the aim is as follows: